PEMBERDAYAAN IRT GAMPONG ALUE BEURAWE MELALUI BUDIDAYA TANAMAN HIDROPONIK SEBAGAI UPAYA PENINGKATAN EKONOMI KELUARGA - Elisa Putri; Tutdin, Zakia; Yusra, Syarifah (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Hydroponic system technology is a method of farming using planting media other than soil, such as pumice, gravel, sand, coconut fiber, pieces of wood or foam. This is done because the function of soil as a support for plant roots and as an intermediary for nutrient solutions can be replaced by flowing or adding nutrients, water and oxygen through this medium. The aim of this community service activity was to provide science and technology to the housewives of Gampong Alue Beurawe regarding the hydroponic system as a solution to the limited agricultural land in Gampong Alue Beurawe. Then, the results of the cultivated vegetables using this hydroponic system can be marketed and become a source of income for partners. The implementation of this activity was carried out in several stages, namely: 1) observation and legalization, 2) implementation of training, 3) practice of cultivating plants using a hydroponic system, and 4) evaluation. From the results of implementing this activity, the target partner has a series of household scale hydroponic systems as a business. Apart from that, target partners also have knowledge and skills in farming using a hydroponic system. The resulting hydroponic plant harvest have been marketed and become income for partners. This activity is expected to be an opportunity for new entrepreneurial partners who will join the business group in the future to keep up with current developments, so that they are able to compete in this globalized world.